Plaque morphological changes after drug-coated balloon angioplasty according to underlying plaque components - Naoki Fujisawa, MD; Takenobu Shimada, MD; Kenichiro Otsuka, MD, PhD; Takanori Yamazaki, MD, PhD; Daiju Fukuda, MD, PhD (Journal of Vascular Surgery Cases and Innovative Techniques)
A 52-year-old man with a short chronic total occlusion in the left superficial femoral artery underwent drug-coated balloon (DCB) angioplasty. Evaluation using integrated backscatter intravascular ultrasound revealed that the plaque volume of fibrosis was compressed just after treatment (from 494.67 mm3 to 398.36 mm3) and was further decreased at 1 month after treatment (to 362.07 mm3). The plaque volume of the lipid pool was not changed at follow-up compared with that just after DCB dilation. These integrated backscatter intravascular ultrasound findings suggest that the effect of DCB angioplasty may differ depending on the type of underlying plaque components.